2011
DOI: 10.1007/s13199-011-0108-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth of foliose lichens: a review

Abstract: This review considers various aspects of the growth of foliose lichens including early growth and development, variation in radial growth rate (RaGR) of different species, growth to maturity, lobe growth variation, senescence and fragmentation, growth models, the influence of environmental variables, and the maintenance of thallus symmetry. The data suggest that a foliose lichen thallus is essentially a 'colony' in which the individual lobes exhibit a considerable degree of autonomy in their growth processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 85 publications
1
48
0
Order By: Relevance
“…Armstrong (1983Armstrong ( , 2005, Haworth et al (1986), Bradwell and Armstrong (2007), and Benedict (2008) all found a general decrease in lichen growth rate with increasing size, after an optimum diameter is surpassed (~30-50 mm). In contrast, Matthews (1994) found no decrease in growth rate in even the largest thalli (>100 mm).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Armstrong (1983Armstrong ( , 2005, Haworth et al (1986), Bradwell and Armstrong (2007), and Benedict (2008) all found a general decrease in lichen growth rate with increasing size, after an optimum diameter is surpassed (~30-50 mm). In contrast, Matthews (1994) found no decrease in growth rate in even the largest thalli (>100 mm).…”
Section: Introductionmentioning
confidence: 88%
“…Bradwell and Armstrong (2007) reported mean diametral growth rates (averaged over 4.33 years) of between 0.6-1.0 mm yr -1 (thalli >10 mm diameter) in maritime southern Iceland. Armstrong's (1983Armstrong's ( , 2005 detailed studies recorded mean growth rates of 1.0-1.5 mm yr -1 in maritime north Wales. Winchester and Chaujar (2002) found similar, but slightly faster (~1.6 mm yr -1 ) growth rates in Capel Curig, North Wales -a site experiencing exceptionally high rainfall.…”
Section: Armstrong 2005; Bradwell and Armstrong 2007mentioning
confidence: 99%
“…Further evidence for a declining phase in growth in larger thalli comes from a recent study of 134 thalli of four crustose lichen species growing at a single site in north Wales (Armstrong 2005b) and a study of R.…”
Section: The Growth Rate-size Curves Of Crustose Lichensmentioning
confidence: 99%
“…In the absence of a suitable growth model for crustose lichens, second-order polynomial curves have been fitted to these data (Armstrong 2005b). However, further growth studies and especially those concentrating on smaller and larger-sized thalli are needed to define the shape of the size-growth curve more accurately.…”
Section: The Growth Rate-size Curves Of Crustose Lichensmentioning
confidence: 99%
“…During lichen transplantation, there are several factors that must be considered for succesful transplantation, they are kind of substrate, climate, abiotic factors (temperature, humidity, light intensity, wind direction and speed, precipitation, etc.) (Armstrong and Bradwell, 2000), techniques of transplantation, and control of transplant (Coppins and Coppins, 2005).…”
Section: Introductionmentioning
confidence: 99%